Optimum climb technique for a jet propelled aircraft - Kelly, L (College of Aeronautics, Cranfield, 1952)
The present method for obtaining a climb technique for jet propelled aircraft do not include the effect of kinetic energy variation with height. By introducing the concept of ‘energy height’ to include the geometric height and the height equivalent of the kinetic energy, a more exact treatment of the optimum technique has been possible. A new method has been suggested for obtaining the energy height climb function. Continues …